2023
DOI: 10.1186/s12883-023-03049-1
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Grey matter volume depletion links to neurological sequelae in post COVID-19 “long haulers”

Abstract: Objective COVID-19 (SARS-CoV-2) has been associated with neurological sequelae even in those patients with mild respiratory symptoms. Patients experiencing cognitive symptoms such as “brain fog” and other neurologic sequelae for 8 or more weeks define “long haulers”. There is limited information regarding damage to grey matter (GM) structures occurring in COVID-19 “long haulers”. Advanced imaging techniques can quantify brain volume depletions related to COVID-19 infection which is important as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 102 publications
(158 reference statements)
1
10
0
Order By: Relevance
“…[68] A decrease in brain volume has also been observed in patients with long COVID. [69] There are functional and anatomical connections between the olfactory bulb and the medial prefrontal cortex (part of the frontal lobe). [70] Toniolo et al have described the SARS-CoV-2 virus as directly targeting the frontal lobes.…”
Section: Neuropsychiatric Manifestations Of Long Covidmentioning
confidence: 99%
“…[68] A decrease in brain volume has also been observed in patients with long COVID. [69] There are functional and anatomical connections between the olfactory bulb and the medial prefrontal cortex (part of the frontal lobe). [70] Toniolo et al have described the SARS-CoV-2 virus as directly targeting the frontal lobes.…”
Section: Neuropsychiatric Manifestations Of Long Covidmentioning
confidence: 99%
“…75 Brain imaging using magnetic resonance imaging and magnetic resonance imaging with diffusion tensor imaging have identified differences in brain structures between patients who have recovered from acute COVID-19 and controls. [78][79][80] In one study, self-reported memory loss correlated with changes in total gray matter volume in general and at specific sites, along with global mean diffusivity of white matter. 79 Patients with neurologic symptoms after acute COVID-19 infection had "bloodbrain barrier (BBB) impairment, elevated microglia activation markers, and a polyclonal B cell response targeting self-antigens and non-self-antigens" 81 along with significantly higher median interferon γ in cerebrospinal fluid.…”
Section: Cognitive Impairment or 2 Orthostatic Intolerancementioning
confidence: 99%
“…A CDC study recently found that risk of newly diagnosed diabetes in children that had been diagnosed with COVID-19 was more than twice as high (Barrett, 2022). Additional long-term impacts of the virus may include brain shrinkage (Rothstein, 2022), cognitive deficits (Hampshire et al, 2022), risk of heart disease and stroke (Sidik, 2022), reduced kidney functioning (Windpessl et al, 2021), liver damage (Wang et al, 2021), and impact on the endocrine system (Somasundaram et al, 2020). Preliminary evidence suggests that more recent variants may be worse for long COVID than earlier strains of the virus (Office for National Statistics, 2022).…”
Section: Introductionmentioning
confidence: 99%